Synthetic small intestinal scaffolds for improved studies of intestinal differentiation. Issue 6 (22nd January 2014) - Costello, Cait M.; Hongpeng, Jia; Shaffiey, Shahab; Yu, Jiajie; Jain, Nina K.; Hackam, David; March, John C.
ABSTRACT In vitro intestinal models can provide new insights into small intestinal function, including cellular growth and proliferation mechanisms, drug absorption capabilities, and host‐microbial interactions. These models are typically formed with cells cultured on 2D scaffolds or transwell inserts, but it is widely understood that epithelial cells cultured in 3D environments exhibit different phenotypes that are more reflective of native tissue. Our focus was to develop a porous, synthetic 3D tissue scaffold with villous features that could support the culture of epithelial cell types to mimic the natural microenvironment of the small intestine. We demonstrated that our scaffold could support the co‐culture of Caco‐2 cells with a mucus‐producing cell line, HT29‐MTX, as well as small intestinal crypts from mice for extended periods. By recreating the surface topography with accurately sized intestinal villi, we enable cellular differentiation along the villous axis in a similar manner to native intestines. In addition, we show that the biochemical microenvironments of the intestine can be further simulated via a combination of apical and basolateral feeding of intestinal cell types cultured on the 3D models. Biotechnol. Bioeng. 2014;111: 1222–1232. © 2014 Wiley Periodicals, Inc.